Genetic polymorphisms and their association with neurobiological and psychological factors in anorexia nervosa: a systematic review - Almaghrbi, Heba; Bawadi, Hiba (Frontiers in Psychology, 2024)
Background and Aims: Anorexia nervosa (AN) is a complex neuropsychiatric disorder. This systematic review synthesizes evidence from diverse studies to assess and investigate the association between gene polymorphisms and psychological and neurobiological factors in patients with AN.Methods: A systematic search across PubMed, PsycINFO, Scopus, and Web of Science databases, along with manual searching, was conducted. The review protocol was approved by PROSPERO (CRD42023452548). Out of 1250 articles, 11 met the inclusion criteria. The quality of eligible articles was assessed using the Newcastle-Ottawa Scale (NOS) tool. The systematic review followed the PRISMA guidelines.Results: The serotoninergic system, particularly the 5-HTTLPR polymorphism, is consistently linked to altered connectivity in the ventral attention network, impaired inhibitory control, and increased susceptibility to AN. The 5-HTTLPR polymorphism affects reward processing, motivation, reasoning, working memory, inhibition, and outcome prediction in patients with AN.The dopaminergic system, involving genes like COMT, DRD2, DRD3, and DAT1, regulates reward, motivation, and decision-making. Genetic variations in these dopaminergic genes are associated with psychological manifestations and clinical severity in patients with AN. Across populations, the Val66Met polymorphism in the BDNF gene influences personality traits, eating behaviors, and emotional responses. Genes like OXTR, TFAP2B, and KCTD15 are linked to social cognition, emotional processing, body image concerns, and personality dimensions in patients with AN.Conclusions: There was an association linking multiple genes to the susceptibly and/or severity of AN. This genetic factor contributes to the complexity of AN and leads to higher diversity of its clinical presentation. Therefore, conducting more extensive research to elucidate the underlying mechanisms of anorexia nervosa pathology is imperative for advancing our understanding and potentially developing targeted therapeutic interventions for the disorder.